P-075 Systematic Review of Evidence for Monoclonal Antibody Biosimilars for the Treatment of Inflammatory Bowel Disease. (February 2017) - Petersel, Danielle; Cheung, Raymond; Sewell, K. Lea; Singh, Ena; Isakov, Leah; Jacobs, Ira
Abstract : Background: Several biosimilars are in development or marketed for a number of chronic inflammatory indications, including Crohn's disease (CD), and ulcerative colitis (UC). Biosimilars are expected to improve patient access to biologics for these chronic conditions. To support awareness and education, healthcare professionals need to understand the evidence base underpinning biosimilar development. Knowledge gaps still exist, e.g., indication extrapolation, interchangeability, substitution, and the totality of evidence which forms the basis for regulatory approval. This study systematically collated all published data for biosimilars for the treatment of inflammatory bowel disease (IBD) to assess the available evidence, to inform and support clinical decision-making. Methods: MEDLINE, Embase and ISI Web of Science were searched to September 2015, and conference proceedings were searched from 2012 to July 2015. Studies disclosing biosimilars with unique identifiers were categorized by originator drug, study type and indication. To assess data strength and validity, risk of bias assessments for observational studies and health economic studies were performed using the Downs and Black tool, and Drummond's checklist, respectively. Results: Similarity trials for biosimilars in the inflammation field have predominately not been conducted in IBD patients. At the cut-off date, only infliximab biosimilar CT-P13 had published data in IBD (N = 336; 7 non-active comparator observational post-approval studies; tumor necrosis factor inhibitor [TNFi] naive and experienced patient cohorts). In one study of 110 patients with Crohn's disease (CD) or ulcerative colitis (UC), clinical response to CT-P13 (Crohn's Disease Activity Index: decrease by ≥70 points; Mayo score: decrease by ≥3 points) at 8 weeks was 87% in TNFi naïve patients and 67% in patients who switched from another TNFi. Another prospective study in 90 patients with CD or UC found decreases in scores of disease activity after 6 weeks of treatment with CT-P13. Three studies (N = 12 [UC only]; 17; 39, respectively) reported similar clinical responses. One indirect comparison study (N = 36) had unfavorable statistically significant outcomes for surgery/hospital readmission rates and steroid augmentation for CT-P13 versus the originator. One cohort study (N = 32) reported a comparable safety profile for CT-P13 in pediatric CD patients switching from the originator. Combined evidence from published health economic studies (n = 3) investigating CT-P13 for IBD (and other chronic inflammatory indications) demonstrated substantial cost savings, with degree of budget impact dependent on patient numbers, eligibility for treatment, acquisition cost and interchangeability between the biosimilar and originator drug. All identified studies were of fair to good quality. Conclusions: This systematic review provides an unbiased synthesis of the available evidence for biosimilars in IBD. Together, the data retrieved from published observational and health economic studies largely support the use of CT-P13 in UC and CD. At the time of analysis, published data from randomized controlled trials in IBD for CT-P13 and other biosimilars (on the market and in development) were lacking. However, the completion of a randomized double-blind parallel group study for CT-P13 versus the originator drug in CD is expected soon. Further studies published in full-text will be required to reliably demonstrate biosimilarity between originators and biosimilars for use in IBD.